Methods of prevention of epidural fibrosis - M. N. Prostomolotov (Acta Biomedica Scientifica, 2013)
It is known, that preservation of ligamentum flavum while microdiscectomy allows to improve results of treatment in patients with lumbal intervertebral disk herniations, promoting prevention of epidural fibrosis that may cause failed back syndrome. Microdiscectomy with flavopreservation with the help of high-speed drill increases possibilities of ligamentum flavum saving while microdiscectomy in a case of narrow interlaminal interval, expressed spondylarthrosis and osteoarthrosis in the lumbosacral vertebral area at different levels and promotes to prevention epidural fibrosis. The offered way of a ligamentum flavum preservations while microdiscectomy differs from existing in carrying out interlaminectomy with the help of high-speed drill by processing of the up- and underlaying vertebras and ligamentum flavum is released from a place of its attachment to bone structures with preservation of its attachment to an inters-pinous ligament in length of 3-4 mm in the site of medial edge of the lamina of an overlying vertebra. The ligamentum flavum is taken away by the ligature and after excision of a disk hernia it comes back to original position and is fixed with surrounding tissues.